2015
DOI: 10.1177/1535370214565976
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of induced pluripotent stem cells for cardiovascular system regeneration

Abstract: Induced pluripotent stem cells (iPSCs) hold great promise for basic research and regenerative medicine. They offer the same advantages as embryonic stem cells (ESCs) and moreover new perspectives for personalized medicine. iPSCs can be generated from adult somatic tissues by over-expression of a few defined transcription factors, including Oct4, Sox2, Klf4, and c-myc. For regenerative medicine in particular, the technology provides great hope for patients with incurable diseases or potentially fatal disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Research has shown the existence of resident cardiac stem cells and their many homeostatic and repairing abilities [ 253 ]. These cells, like all the rest, undergo aging and as such they lose their self-renewing ability ultimately leading to overall cardiac aging and as mention before to a reduction of cardiac function [ 254 , 255 ]. Obviously, an intervention on these cells such as their replacement/transplantation or enhancement through factor-based therapies could be an innovative way to reduce overall cardiac aging.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown the existence of resident cardiac stem cells and their many homeostatic and repairing abilities [ 253 ]. These cells, like all the rest, undergo aging and as such they lose their self-renewing ability ultimately leading to overall cardiac aging and as mention before to a reduction of cardiac function [ 254 , 255 ]. Obviously, an intervention on these cells such as their replacement/transplantation or enhancement through factor-based therapies could be an innovative way to reduce overall cardiac aging.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic cells such as fibroblasts or keratinocytes that are easy to obtain could be reprogrammed into iPSCs, which could then be differentiated into cardiomyocytes or other cell lineages [ 120 ]. However, the inherent challenges associated with the reprogramming of somatic cells into iPSCs and requirement of excellent purification systems [ 130 ] limit their widespread use at present.…”
Section: Biofabrication For Congenital Cardiac Surgerymentioning
confidence: 99%
“…A correct representation of BM, in terms of its composition, structure, and function becomes necessary to successfully utilize the developmental precursor approach. Also, the in vitro or in vivo differentiation of stem cells into CMs pre- or post-printing mimics the sequential stages of embryonic cardiac development [ 130 ]. Hence, in addition to replicating the BM by bioprinting, incorporation of three important families of growth factors that play an essential role in cardiogenesis in the right quantities and form becomes necessary.…”
Section: Biofabrication For Congenital Cardiac Surgerymentioning
confidence: 99%
“…Since this breakthrough, various opportunities for application have been reported in cell therapy, modeling of new diseases, and studies of complex genetic features and allelic variations, as substrates for drug, in toxicity, differentiation, and regenerative medicine therapies, and in therapeutic screening [77, 78]. In addition, using the iPSCs, it is possible to differentiate into patient- and disease-specific cell types.…”
Section: Cardiovascular Diseases and Stem Cellsmentioning
confidence: 99%